Preparation and Applications of Pseudopeptide-Based Nanomaterials - Milli, Lorenzo <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
This thesis describes the synthesis, the conformational analysis and the applications of pseudopetide foldamers containing the 4-carboxy-5-methyl-oxazolidin-2-one moiety or the pyroglutamic acid unit. These molecules mimic a proline group and have been applied to the formation of oligomers that in solution may easily adopt a stable secondary structure. These pseudoprolines block the peptide bond always in the trans conformation, because the nitrogen atom of the ring is adjacent to both an exocyclic and an endocyclic carbonyl group, forcing them to a strict trans conformation. This remarkable property induces a constrain in the pseudopeptide chain that may help the formation of supramolecular materials. Following a simple methodology we have efficiently prepared a variety of foldamers, whose proprieties may be changed choosing different amino acids, thus providing several secondary structures.